SOIL CARBON STOCKS AND LABILE FRACTIONS OF ORGANIC MATTER UNDER DIFFERENTS VEGETATIONS COVERAGES IN GURUPI – TO - Marinho Junior, Josue Luiz; de Araújo Filho, Renisson Neponuceno; Cunha Filho, Moacyr; Gomes Filho, Raimundo Rodrigues; Fernandes, Milton Marques; Piscoya, Victor Casimiro (Floresta, 2021)
Soils represent a large reservoir of carbon (C), and changes in use and management can impact C balance and global climate control. The study aimed to determine the effect of changes in vegetation cover on soil C stocks and labile fractions in the Cerrado biome in the southern region of Tocantins. The work was developed in areas of Eucalyptus sp., pasture, agriculture and cerrado sensu stricto at the experimental farm in Federal University of Tocantins. The soil samples were collected in trenches of 70 x 70 cm at depths 0-10, 10-20, 20-30, 30-40 and 40-50 cm, with six replications. Statistical analysis was performed using the normality test, analysis of variance and comparison of means by the Tukey test at 5% significance. On Eucalyptus stands, the soil’s carbon was higher than native forest vegetation, pasture and agriculture. The contents of labile carbon (C-labile) and light organic matter (LOM) were 26.80 and 41.58% higher for the Eucalyptus sp. compared to native forest, 25.75 and 35.76% for pasture, and 48.39 and 9.50% for agriculture, respectively. Among the different areas evaluated, it was found that Eucalyptus sp. it has great potential to increase the carbon storage in the soil, C-labile and light organic matter.